Combined Experimental and Theoretical Approach to the Kinetics of Magnetite Crystal Growth from Primary Particles - Widdrat, Marc (J Phys Chem Lett, 2017)
[Image: see text] It is now recognized that nucleation and growth of crystals can occur not only by the addition of solvated ions but also by accretion of nanoparticles, in a process called nonclassical crystallization. The theoretical framework of such processes has only started to be described, partly due to the lack of kinetic or thermodynamic data. Here, we study the growth of magnetite nanoparticles from primary particles—nanometer-sized amorphous iron-rich precursors—in aqueous solution at different temperatures. We propose a theoretical framework to describe the growth of the nanoparticles and model both a diffusion-limited and a reaction-limited pathway to determine which of these best describes the rate-limiting step of the process. We show that, based on the measured iron concentration and the related calculated concentration of primary particles at the steady state, magnetite growth is likely a reaction-limited process, and within the framework of our model, we propose a phase diagram to summarize the observations.